1975
DOI: 10.5935/0305-7518.19750044
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Leprosy with Clofazimine, Rifampicin and Bayrena

Abstract: In Africa, 8% of leprosy patients have the lepromatous form, and 85% have the tuberculoid form of the disease. Treating these patients with dapsone needs severa] years to produce good results, treatment with acedapsone is still in the experimental st age, and rifampicin is too expensive. There are two drugs remaining; clofazimine, which is the treatment of choice for those with lepromatous leprosy, and sulphanilamides, treatment for the tuberculoid form of leprosy and for acute inflammation af the peripheral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…We agree with Languillon [30], Basset and Samsoen [7] and Coudert et at. [10], that certain sulfonamides are good antileprotic drugs.…”
Section: New Combinations Including Sulfonamidessupporting
confidence: 82%
“…We agree with Languillon [30], Basset and Samsoen [7] and Coudert et at. [10], that certain sulfonamides are good antileprotic drugs.…”
Section: New Combinations Including Sulfonamidessupporting
confidence: 82%
“…In the course of this study, we identified two compounds, including sulfameter and mexenone, that bind to sialidase-1. Sulfameter is an old antibacterial drug that has been used in the treatment of leprosy 26 and urinary tract infections, 27 while mexenone is an active sun screen agent. 28 These compounds have not been previously reported in the literature to bind to sialidase-1, nor are they represented in the machine learning model training set.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…■ Very good results were observed with the combination of dapsone and rifampicin, and there were some evidence of the equivalence of once a month rifampicin with everyday regimen [30][31][32];…”
Section: Who Multidrug Therapy: Rationale Evidence and Criticismsmentioning
confidence: 92%